The effects of metallic Si addtions on the synthesis of beta-SiC powders using a sol-gel method - Kim, Gyu-Mi; Cho, Gyung-Sun; Lim, Dea-Soon; Park, Sang-Whan (KOREAN ASSOC CRYSTAL GROWTH, INC, 2010)
Single phase beta-SiC powders were synthesized using SiO2/C hybrid precursors with and without the addition of metallic Si powders. The SiO2/C hybrid precursors with various C/Si mole ratios (1.6-4.0) were prepared by a sol-gel process using tetraethyl orthosilicate and phenol resin as starting materials. Fine beta-SiC powders were synthesized by the carbothermal reduction of the SiO2/C hybrid precursor with and without the addition of metallic Si powders in the temperature range between 1250 degrees C-1800 degrees C under a vacuum atmosphere. Single phase beta-SiC powders were obtained by the carbothermal reduction of the SiO2/C hybrid precursor with a C/Si mole ratio of 1.6 above 1600 degrees C under a vacuum atmosphere. It was found that the addition of metallic Si powders to the the SiO2/C hybrid precursor with excess carbon reduced the temperature for the synthesis of single phase beta-SiC powders to as low as 1350 degrees C. The particle sizes of synthesized beta-SiC powders from the metallic Si powder added SiO2/C hybrid precursor with excess carbon were less than 1 mu m, in which fine beta-SiC powders appeared to be slightly aggregated.
Keywords: SILICON-CARBIDE POWDERS; CARBOTHERMAL REDUCTION